Age and density of eggs of Helicoverpa armigera influence on Trichogramma pretiosum parasitism - Zuim, Vitor; Rodrigues, Hígor de Souza; Pratissoli, Dirceu; Torres, Jorge Braz; Fragoso, Débora Ferreira Melo; Bueno, Regiane Cristina Oliveira de Freitas [UNESP] (Universidade Estadual de Maringa, 2017)
This study evaluated the parasitism of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) on eggs of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) at different ages and densities. The rates of parasitism and emergence, the number of parasitoids emerged per egg and sex ratio of offspring were evaluated in both experiments. Eggs of H. armigera up to 36 hours provided greater parasitism and emergence of adults compared to eggs up to 60 hours old. The number of parasitoids, which emerged per host egg, was greater than one and the sex ratio remained around 80% of females, regardless of the egg development stage. Females of T. pretiosum responded with superior rates of parasitism, emergence and number of parasitoids per egg at the densities of 20 and 25 eggs of H. armigera. These results indicate that T. pretiosum parasite with superior performance in eggs of up to 36h of age and densities of 20 eggs per female day-1 in laboratory conditions. These results will help to establish the intervals between releases of parasitoids, aiming to control this pest, when adjusted with knowledge of the survival of the parasitoids in the field and in pest infestation.
Influência da idade e densidade de ovos de Helicoverpa armigera no parasitismo de Trichogramma pretiosum
Keywords: Biological control; Egg parasitoid; Exotic pest; Host-parasitoid interaction; Noctuidae